Pien Tze Huang attenuated acetaminophen-induced liver injury by autophagy mediated-NLRP3 inflammasome inhibition. (15th July 2023) - Zhao, Ruowei; Zhang, Qing; Liu, Wenjing; Lin, Yifan; He, Yuhui; Chang, Dennis; Li, Shaohua; Xu, Wen; Lin, Yanxiang; Zheng, Yanfang; Zhou, Xian; Huang, Mingqing
Abstract: Ethnopharmacological relevance: Pien Tze Huang is a classic traditional Chinese medicinal product, used for inflammatory diseases as stated in Chinese Pharmacopoeia. In particular, it is effective in treating liver diseases and pro-inflammatory conditions. Acetaminophen (APAP) is a widely used analgesic drug, but its over-dose is associated with acute liver failure where the clinical approved antidote treatment is limited. Inflammation has been considered as one of the therapeutic targets against APAP-induced liver injury. Aim of the study: We aimed to explore the therapeutic potential of Pien Tze Huang tablet (PTH) on protecting liver against APAP-induced liver injury through its strong anti-inflammatory pharmacological action. Materials and methods: Wild-type C57BL/6 mice were given PTH (75, 150 and 300 mg/kg) by oral gavage 3 days before the APAP injection (400 mg/kg). The protective effect of PTH was assessed by aspartate aminotransferase (AST) and alanine transaminase (ALT) levels and pathological staining. The mechanisms underlying PTH's hepatoprotective effects were investigated in nucleotide-binding domain (NOD)-like receptor protein 3 (NLRP3) knock-out (NLRP3 −/− ), over expression NLRP3 (oe-NLRP3) mice, and wild-type mice with the injection of autophagy inhibitor (3-methyladenine, 3-MA). Results: APAP-exposed mice resulted in evident liver injury which was evidenced by hepatic necrosis and elevated levels of AST and ALT in the wild-type C57BL/6 mice. PTH dose-dependently reduced ALT, AST and upregulated autophagy activity. In addition, PTH significantly reduced elevated levels of proinflammatory cytokines and NLRP3 inflammasome. The liver protective effect of PTH (300 mg/kg) was still obvious in the oe-NLRP3 mice, however, it became insignificant in the NLRP3 −/− mice. When PTH (300 mg/kg) was co-treated with 3-MA to the wild-type C57BL/6 mice, the NLRP3 inhibition were reversed when autophagy was blocked. Conclusion: PTH exerted a beneficial effect in protecting liver against APAP-induced liver injury. The underlying molecular mechanism was associated with the NLRP3 inflammasome inhibition which was likely driven by the upregulated autophagy activity. Our study underpins the traditional use of PTH in protecting liver through its anti-inflammatory action. Graphical abstract: Image 1 Highlights: Pien Tze Huang tablet (PTH) protected liver against acetaminophen-induced liver injury. PTH suppressed liver inflammation induced by overdose acetaminophen. The antidote mechanism is associated with nucleotide-binding domain (NOD)-like receptor protein 3 (NLRP3) inflammasome inhibition. PTH's NLRP3 inhibition was driven by the upregulated autophagy.